Development and advocacy: selected essays from development in practice - Eade, Deborah (ed.); Introduced by Maria Teresa Diokno-Pascual (Oxford, 2002)
Most major development NGOs dedicate significant resources to advocacy. Many also work to inform and shape public opinion, whether through advertising or fundraising or through education programmes. They argue that fundamental change is not achieved until the policy environment is right and cannot be sustained without a groundswell of support for reform. In recent years, however, advocacy work has come under increasing criticism. NGOs are challenged on the grounds of: Legitimacy - Whom do they represent, and to whom are they accountable? Effectiveness - What practical impact does high-level advocacies have on the lives of people living in poverty and who is to judge this? Role - Should NGOs try to combine funding and advocacy or do these demand different kinds of South-North relationship? Strategy - Are NGOs seduced by agencies like the World Bank or by the corporate sector to readily? When does constructive engagement with these powerful bodies turn into co-option by them? As international grassroots advocacy is becoming more vocal thanks to new communication technologies; what is the appropriate role for Northern NGOs?
Keywords: Economic development